Treating early‐stage Hodgkin lymphoma in resource‐limited settings: InPOG‐HL‐15‐01 experience. Issue 10 (22nd July 2021) - Mahajan, Amita; Singh, Manisha; Bakhshi, Sameer; Jain, Sandeep; Radhakrishnan, Venkatraman; Verma, Nishant; Seth, Rachna; Arora, Ramandeep Singh; Dinand, Veronique; Kalra, Manas; Mandal, Piali; Kapoor, Gauri; et al.
Abstract: Background: Hodgkin lymphoma (HL) in childhood is an eminently curable disease. Excellent outcomes can be achieved even in resource‐limited settings and increasingly, the focus is on limiting long‐term toxicity. Contemporary treatment incorporates a risk‐stratified, response‐adapted approach using multiagent chemotherapy with or without low‐dose radiotherapy (RT). Many developing countries continue to use ABVD (adriamycin, bleomycin, vinblastin, and dacarbazine)‐based regimen owing to limited acute toxicity, cost, and ease of delivery. We report outcomes of children with early‐stage HL using limited cycles of ABVD‐based treatment in the first prospective multicentric collaborative study from India InPOG‐HL‐15‐01. Methods: Children <18 years with biopsy‐proven HL were enrolled. Patients with stages I and IIA with or without bulky disease were classified as having early‐stage disease. Patients were planned to receive four cycles of ABVD subject to satisfactory early response assessment (ERA) scheduled after two cycles of chemotherapy. RT was limited to patients with bulky disease or those with suboptimal ERA. Results: Four hundred ten patients were enrolled over 30 months from 27 centers. One hundred thirty‐four were classified as having early‐stage disease. Fifty‐three (40%) of these had bulky disease. One hundred ten (83%) of this cohort achieved complete or very good partial ERA. Fifty‐four (40%) received RT. At a median of 52 months since diagnosis, 5‐year event‐free survival (EFS) and overall survival (OS) is 94% and 95.5%, respectively. Treatment‐related mortality and abandonment were <1%. Conclusion: Limited cycles of ABVD with RT to selected patients is a very effective option for patients with early‐stage disease in resource‐limited settings.